Combining multi-scale surface texturing and DLC coatings for improved tribological performance of 3D printed polymers - Marian, Max; Zambrano, Dario; Rothammer, Benedict; Waltenberger, Valentin; Boidi, Guido; Krapf, Anna; Merle, Benoit; Stampfl, Juergen; Rosenkranz, Andreas; Gachot, Carsten; Grützmacher, Philipp (Surface & Coatings Technology, 2023)
Polymer components fabricated by additive manufacturing typically show only moderate strength and low temperature stability, possibly leading to severe wear and short lifetimes especially under dry tribological sliding. To tackle these shortcomings, we investigated the combination of single- and multi-scale textures directly fabricated by digital light processing with amorphous diamond-like carbon (DLC) coatings. The topography of the samples and conformity of the coatings on the textures are assessed and their tribological behaviour under dry conditions is studied. We demonstrate that the surface textures have a detrimental tribological effect on the uncoated samples. This changes with the application of DLC coatings since friction substantially reduces and wear of the textures is not observed anymore. These trends are attributed to the protection of the underlying polymer substrate by the coatings and a reduced contact area. The best tribological performance is found for a coating with highest hardness and hardness-to-elasticity ratios. Moreover, multi-scale textures perform slightly better than single-scale textures due to a smaller real contact area. Summarizing, we verified that the high flexibility and low production costs of 3D printing combined with the excellent mechanical and tribological properties of DLC results in synergistic effects with an excellent performance under dry sliding conditions.<br